Effect of high pressure on growth of colloidal particles during sol–gel phase transition of resorcinol–formaldehyde solution - Yamamoto, T.; Tayakout-Fayolle, M.; Iimura, K.; Satone, H.; Kakibe, T.; Itoh, K.; Maeda, K. (Adsorption : journal of the International Adsorption Society, 2019)
We examined the effect of high pressure on the sol–gel phase transition of a resorcinol–formaldehyde (RF) aqueous solution to a RF hydrogel, which was hold under a certain pressure varied in the range from the ambient pressure to 400 MPa. By employing the dynamic light scattering method, we analyzed the scattered intensity of a He–Ne laser which was irradiated to the RF solution to determine the hydrodynamic diameter of the structure formed during the phase transition. Before the completion of the phase transition, we measured the transient change in the size of colloidal particles, i.e. the unit of the porous structure formed in the RF hydrogel. It was revealed that the size of the colloidal particles increased with the increase in the pressure added to the RF solution. After the completion of the phase transition, we prepared a RF cryogel by removing solvent from a RF hydrogel by freeze-drying. The specific surface area of the RF cryogel was found to decrease with the increase in the added pressure, as a result of the increase in the size of the unit of the porous structure.